Letter from William Meridith to James Curtis Booth - Meridith, William (1861)
Letter to James Curtis Booth (1810-1888) stating "you are so eminently qualified for the position which you now hold in the Mint, that I am very sure that the idea of removing you, if entertained at all, must be founded on some mistake."
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States